Normal Hemoglobin Values in 12-24 Month Old Children - Zahedi Affandi; Harry Respati; Ponpon Ijradinata (Indonesian Pediatric Society, 1995)
One hundred and thirty-one children aged 12 to 24 months attending the Under Five Clinic of The Department of Child Health, Medical School, Padjadjaran University/Hasan Sadikin General Hospital in Bandung were studied. These subjects were